Measuring respirator use in the workplace - Kalsbeek, William D., 1946-; Plewes, Thomas J.; McGowan, Ericka (National Academies Press, 2007)
"As part of a multifaceted look at the inherited and evolving portfolio of the National Personal Protective Technology Laboratory (NPPTL), the laboratory asked the National Academies to undertake a special look at the informational underpinnings of the NPPTL program to promote effective use of respirator equipment in the workplace. The primary focus of the committee inquiry was to be on a landmark survey conducted by the Bureau of Labor Statistics (BLS) and the National Institute for Occupational Safety and Health (NIOSH)--the 2001 Survey of Respirator Use and Practices (SRUP)." - p. 1.